A política militar sob Geisel na cobertura do jornal Folha de S. Paulo, 1974-1979 - Carvalho, Flávia Sanches de (2021)
This thesis deals with the peculiarities of the military way of doing politics, based on its own codes that take into account hierarchy, leadership relations, and loyalty to arms, through the analysis of the journalistic coverage of the military environment by the newspaper Folha de S. Paulo, between the years 1976 and 1979, during the administration of general Ernesto Geisel (1974-1979). Thus, the objective of this work is to trace and systematize, based on specialized journalistic coverage, the relations and networks of power in the Armed Forces and their articulations in the government of Ernesto Geisel, especially with regard to the processes of opening and presidential succession that elected the last military government. For this purpose, the work approaches two themes related to the military regime: the relations of the press with the government, and the military politics itself, marked by internal conflicts in the Armed Forces. Methodologically, we analyzed the published articles related to the theme in the period in question and the internal reports prepared by the journalist Ana Lagôa to support the published articles. Using this material as primary and secondary sources, it was verified that, contrary to the idea of military unity of the regime constructed by the military for the period, the government of President Geisel was marked by intense internal disputes, political struggles and power articulations within the Armed Forces that tensioned and interfered in both the presidential succession and the opening process.